2014
DOI: 10.1002/phar.1483
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Glucose Change in Hypertensive Participants Following Short-term Treatment with Atenolol or Hydrochlorothiazide

Abstract: Study Objective To develop and validate a predictive model for glucose change and risk for new-onset impaired fasting glucose in hypertensive participants following treatment with atenolol or hydrochlorothiazide (HCTZ). Design Randomized multicenter clinical trial. Patients A total of 735 white or African-American men and women with uncomplicated hypertension. Measurements and Main Results Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) is a randomized clinical trial to assess the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…The analysis was adjusted for age, sex, and baselines glucose because these were associated with the change in glucose post chlorthalidone treatment in our study. Also, studies have shown baselines glucose to be a significant predictor of thiazide‐associated glucose change . Furthermore, even though we did not find any population substructure in our cohort, principal components 1 and 2 were included in the model to account for ancestry.…”
Section: Methodsmentioning
confidence: 84%
“…The analysis was adjusted for age, sex, and baselines glucose because these were associated with the change in glucose post chlorthalidone treatment in our study. Also, studies have shown baselines glucose to be a significant predictor of thiazide‐associated glucose change . Furthermore, even though we did not find any population substructure in our cohort, principal components 1 and 2 were included in the model to account for ancestry.…”
Section: Methodsmentioning
confidence: 84%
“…The cause of the increase in uric acid can likely be explained by the addition of hydrochlorothiazide, because elevated uric acid is a common side effect of diuretics. 4 These adverse events were manageable and did not pose a health risk.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that participants with lower baseline glucose measures exhibited the largest variation in glucose after antihypertensive drug exposure (Moore et al 2014). Therefore, participants with impaired fasting glucose (IFG), defined as baseline fasting glucose levels ≥100 mg/dL, were excluded from our metabolomics analysis in order to observe the maximum effect of antihypertensive treatment on glucose level.…”
Section: Methodsmentioning
confidence: 99%